Défendre le corps des femmes. Libre pensée et féminisme aux États-Unis (1820-1920) - Auréliane Narvaez (Transatlantica)
The nineteenth century has long been conceived as a critical period of the history of the United States for women whose religious beliefs motivated their commitment to reform; conversely, women activists who publicly rejected the authority of churches and positive theologies have gone almost entirely unnoticed. As a result, the feminism suffused with anarchist overtones which emerged at the turn of the twentieth century may appear almost fortuitous as its historicity seems untraceable. The historiographic gap regarding women’s role in the promotion of radical freethought thus hinders our understanding of anti-conformist feminist activism predating the 1840s and the first women’s suffrage organizations. This blind spot in the history of women and religion obscures the relationship between feminism and the American freethought tradition throughout the nineteenth century, whose demands were not limited to suffrage. Exploring the lives and ideas of such freethinkers as Frances Wright, Ernestine Rose, Juliet Stillman Severance, Lois Waisbrooker, or Voltairine de Cleyre illuminates the existence of a feminism which ties male domination to the power of religious apparatuses and defends emancipation as well as equal rights by arguing against the essentialization of women.